PENGEMBANGAN E-LEARNING UNTUK MATA PELAJARAN LITERASI DIGITAL - Karmelita, Mita; Susanti, Deffy; Suhendri (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
The development of digital technology requires vocational high school students to have adequate digital literacy for more effective learning. At Bhakti Kencana Jatiwangi Health Vocational High School, low digital literacy and limited use of technology hinder the learning process. To address this, e-learning was developed as a digital literacy learning tool. This system allows students to access materials and take quizzes interactively, while providing a more flexible and engaging learning experience. Features include material management, quiz creation, and the role of administrators in verifying and publishing content. The development results indicate that e-learning can support student engagement, facilitate teacher learning management, and create a more adaptive and interactive learning process. This approach is expected to be an innovative strategy to improve the quality of vocational learning, while being relevant to educational needs in the digital era.